Acute Dystonia Associated with Low-Dose Aripiprazole in a Male Child: A Case Report - Bharat Udey; Jawahar Singh; Jagriti Bhatia (Journal of Clinical and Diagnostic Research, 2024)
Aripiprazole is a newer anti-psychotic agent with low liability for Extrapyramidal Symptoms (EPS). Acute dystonia develops due to a lack of dopamine, resulting in a relative overactivity of cholinergic neurons. In the past, cases of Aripiprazole-induced acute dystonia have been reported more frequently among adults than children. Here, the authors present a case in which acute dystonia developed at a very low dose (2 mg) of Aripiprazole. The case involves a 10-year-old boy diagnosed with Oppositional Defiant Disorder (ODD) who exhibited aggressive behaviour and irritability. Aripiprazole (2 mg) was initiated for treatment, but after five days, the patient developed excessive sleepiness, slurred speech, oculogyric crisis, and torticollis, indicative of acute dystonia. To rule out any organic causes, a detailed assessment and investigations were conducted, including complete blood counts, liver and kidney function tests, serum calcium, electrolytes, ceruloplasmin, blood copper levels, slit-lamp examination for Kayser-Fleischer ring, and electroencephalography, which did not reveal any significant organic conditions. Aripiprazole was discontinued, and Promethazine was administered. The dystonia score on the Unified Dystonia Rating Scale (UDRS) decreased from 10 to 0 in 5 days, indicating complete resolution of dystonia. Naranjo’s causality assessment score was seven, reflecting the probable association of aripiprazole with acute dystonia. This case emphasises the importance of monitoring for adverse reactions to anti-psychotic medications, particularly in paediatric patients, and the need for prompt recognition and management of adverse effects to ensure patient safety and treatment efficacy. To the best of our knowledge, this is the first case report of acute dystonia in a child at such a low dose of Aripiprazole. Clinicians should be vigilant for the emergence of such significant adverse effects of commonly used drugs.